Peningkatan Kreativitas Mahasiswa Dalam Pembuatan Alat Peraga IPA Menggunakan Pembelajaran Berbasis Proyek - Dea Mustika; Febrina Dafit; Vany Sinthya (STAI Terpadu Yogyakarta, 2020)
This research is a classroom action research. This study aimed to describe the improvement of student creativity in the creation ofscience teaching aids using project-based learning. Stage of research includes planning, action, observation and reflection. The subjects of this study were students of the fourth semester class A which consists of 43 students. Data collected using observation sheet and test question. Data were analyzed descriptively. The results of the study showed that there was an increase in student creativity in making science teaching aids using project-based learning